UJI AKTIVITAS ANTIBAKTERI EKSTRAK DAUN SEREH WANGI TERHADAP PERTUMBUHAN BAKTERI STREPTOCOCCUS MUTANS - Ulfayani Mayasari; Alfi Sapitri (KLOROFIL: Jurnal Ilmu Biologi dan Terapan, 2019)
The lemongrass plants (Cymbopogon nardus) is one of the plants used as medicine such as strep throat, cough and colds. The purpose of this study was to determine whether the juice of fragrant lemongrass leaves has antibacterial activity against Streptococcus mutans bacteria that cause dental caries. The research method used is experimental with agar diffusion. The experiment consisted of four treatments namely at concentrations of 20%, 30%, 40% and 50% with three repetitions. The results showed fragrant lemongrass leaves at concentrations of 10%, 20%, 30% and 40% had an average inhibition zone diameter of 14,2 mm, 15,1 mm, 16,2 mm dan 17,3 mm. Fragrant lemongrass leaves can inhibit the growth of Streptococcus mutans.Keywords : Cymbopogon nardus, Antibacterial, Streptococcus mutans.